1985
DOI: 10.1136/jnnp.48.2.137
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological evaluation of mild head injury.

Abstract: SUMMARY Neuropsychological deficits following mild head injury have been reported recently in the literature. The purpose of this study was to investigate this issue with a strict methodological approach. The neuropsychological performance of 50 mildly head injured patients was compared with that of 50 normal controls chosen with the case-control approach. No conclusive evidence was found that mild head injury causes cognitive impairment one month after the trauma.Effects of head injury on mental functions hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
0
1

Year Published

1994
1994
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(59 citation statements)
references
References 13 publications
5
53
0
1
Order By: Relevance
“…The finding that mild TBI participants showed deficits in selective and sustained attention is consistent with a number of studies that have reported problems with attention (e.g., Gentilini et al, 1985Gentilini et al, , 1989Mclean et al, 1983;Stuss et al, 1989). The poorer verbal memory of the mild TBI group also confirms the findings of previous studies undertaken with mild TBI patients (e.g., Dikmen et al, 1986;Stuss et al, 1985).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The finding that mild TBI participants showed deficits in selective and sustained attention is consistent with a number of studies that have reported problems with attention (e.g., Gentilini et al, 1985Gentilini et al, , 1989Mclean et al, 1983;Stuss et al, 1989). The poorer verbal memory of the mild TBI group also confirms the findings of previous studies undertaken with mild TBI patients (e.g., Dikmen et al, 1986;Stuss et al, 1985).…”
Section: Discussionsupporting
confidence: 82%
“…However, objective assessments of memory have provided mixed findings. Whereas Gentilini et al (1985), Levin et al (1987), and Mathias and Coats (1999) found no evidence to indicate visual or verbal memory problems at 1 month post injury, other studies have shown significantly poorer working memory (Newcombe et al, 1994) and delayed recall (Dikmen et al, 1986) at similar post-injury intervals. Prob-lems with verbal learning (Leininger et al, 1990) and delayed recall (Stuss et al, 1985) have additionally been reported in chronically affected mild TBI patients at 3 and 5 months post injury, respectively.…”
Section: Introductionmentioning
confidence: 83%
“…For example, mild injuries show an early rapid change followed by a decelerating rate of improvement over the 1st or 2nd months post injury (Gronwall, 1977(Gronwall, , 1989Gronwall & Wrightson, 1974). Recovery periods ranging from 1 to 3 months have been reported for some attentional skills (Gentilini, Nichelli, Schoenhuber, Bortolotti, Tonelli, Falasca & Merli, 1985;Hugenholtz, Stuss, Stethem & Richard, 1988;Levin, Mattis, Ru, Eisenberg, Marshall, Tabadoor, High & Frankowski, 1987).…”
Section: Introductionmentioning
confidence: 95%
“…Persons with severe TBI are more likely to suffer cognitive and physical impairment compared with those with mild TBI (Dikmen et al, 1986(Dikmen et al, , 1995Gentilini et al, 1985;Gronwall and Wrightson, 1974). Multidisciplinary teams commonly provide coordinated care for those with severe TBI (Brasure, 2012;Sander and Constantinidou, 2008;Wertheimer et al, 2008).…”
Section: Types Of Tbi Rehabilitation Servicesmentioning
confidence: 99%